The Acquisition of Noun Vocabulary in Children Due to the Influence of Game Player Videos on YouTube - Raja Syamsidar; Amron Zarkasih Ritonga; Siti Zubaidah; Ayu Andini; Muji Endah Palupi (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid development of information and communication technology has significantly influenced children’s language acquisition, particularly through digital platforms such as YouTube. This study aims to analyze the acquisition of noun vocabulary in elementary school children resulting from exposure to gamer videos on YouTube from a psycholinguistic perspective. The research employed a qualitative descriptive method involving five children who frequently watched gaming content on YouTube. Data were collected through participant observation, in-depth interviews, recording techniques, and note-taking methods, while analysis was conducted using matching and distributional methods based on Chomsky’s cognitive theory and psycholinguistic approaches. The findings revealed that children experienced notable improvement in noun vocabulary acquisition, especially concrete and abstract nouns related to games, characters, objects, and virtual environments. The children actively applied the newly acquired vocabulary in daily conversations and social interactions, demonstrating meaningful contextual understanding. Gamer videos provided rich visual and verbal stimuli that facilitated children’s comprehension and retention of vocabulary. Furthermore, parental responses indicated that digital media could positively support language development when accompanied by appropriate supervision. This study concludes that YouTube gamer videos contribute significantly to children’s noun vocabulary acquisition and function as an alternative medium for language learning in the digital era.